Cholinesterase Activity on Palm Oil Plantation Workers in Parenggean, Kotawaringin Timur - Suratno Suratno; Dwi Purbayanti; Hildayanti Hildayanti (Jurnal Surya Medika (JSM), 2018)
Use of pesticide is widely used in palm oil plantation industry. Pesticide exposure can affect pesticide-spraying workers' health. This study aimed to determine acetylcholinesterase enzyme (AChE) activity levels and identify of poisoning risk factors on pesticide-spraying workers in a palm oil plantation Comanditaire Venootschap (CV) unit in Parenggeran, Kotawaringin Timur, Central Kalimantan. The cross-sectional study design was conducted to examine cholinesterase enzyme activity levels on 15 pesticide-spraying workers. The cholinesterase levels were measured using an automated photometric technique. This study found that all workers have normal cholinesterase activity levels. The average cholinesterase activity levels were 7065,36 U/L and 6528 U/L, respectively for male and female workers. It was also found that two male workers cholinesterase activity levels of using glyphosate pesticide were almost close to the lower limit of the normal levels range, 4720 U/L, and 4958 U/L, respectively. Use of Personal Protective Equipment (PPE) during the pesticide spraying and maximum time allowed of pesticide spraying in a day have to be considered as an important rule to avoid excessive pesticide exposure.